MATERIAL COMPOSITION, ISOTOPIC-GEOCHRONOLOGICAL STUDIES AND METALLOGENIC POTENTIAL OF GRANITES OF THE KHOTUGU-EYEKIT MASSIF AND RHYOLITE DIKE OF THE SOLOLI UPLIFT - A. I. Ivanov; B. B. Gerasimov; M. S. Ivanov; A. I. Zhuravlev; D. A. Vasiliev; A. I. Kondratiev (Геодинамика и тектонофизика, 2024)
The paper describes the petrographic and petro-geochemical composition of granitoids of the Khotugu-Eyekit massif and the rhyolite dike of the Sololi uplift. It was revealed that the rocks of the massif are represented by microcline granites. The massif is monotonous in composition, i.e. it does not exhibit any facies transitions or differences in intrusion phases. In addition to the massif rocks, the study area is characterized by a widespread occurrence of small bodies of rhyolite dike rocks that have been strongly altered by secondary processes. An assumption was made about the pre-granitoid origin of these dikes and their intensive post-magmatic alteration. Based on the content of basic petrooxides, its ratios and relationships, as well as indicator petrochemical coefficients, it was concluded that the rocks of the Khotugu-Eyekit massif are most similar to the A2-type plumasite granites of the high-potassium calc-alkaline petrochemical series. The main geochemical criteria indicate the dual nature of the granites of the Khotugu-Eyekit massif, which are similar to the granitoids of the collisional formation setting of the area, and their petrogenesis is apparently associated with both mixed crust-mantle and purely crustal source. The same compositional parameters suggest that the rhyolite dike belongs to low-alkaline formations of the tholeiitic series, corresponding to those of the plumasite rare metal series of the crustal nature. The U-Pb dating yielded an absolute age of 2146±13 Ma for the rhyolite dikes; the same method and the geological data imply that the Khotugu-Eyekit massif is Mesozoic in age, dating back to 186.7–157.2 Ma. Mineragenic specialization analysis of the Khotugu-Eyekit massif and the rhyolite dike, performed on the basis of the geochemical data, allows classifying the studied formations as productive in terms of gold-bearing ore formations.